Monitoring of carbon steels welded joints by magnetic Barkhausen noise (2015)
ABSTRACT: When a variable magnetic field is applied to a ferromagnetic material, it has been observed that, next to the coercive field (Hc), rise in induction (B) takes place through abrupt jumps known as Barkhausen jumps. In this research, the microstructure variation in carbon steel welded joints was monitored by the Magnetic Barkhausen Noise (MBN). The samples were welded by SMAW process, in which both one-pass and two-pass were applied. Microhardness and microstructure were also characterized. The MBN signal was measured and analysed by means of several frequency and time domain parameters. Furthermore, maps of the welded steel surfaces were plotted. The variation of the MBN parameters was correlated to those of the microhardness and microstructure. The results allowed identifying a heat-affected zone (HAZ) of the welded joint using the MBN signals